Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Zhou, Xiaoyan; Ning, Yue; Xie, Jingyi; Han, Yi; Tang, Chaonan; Su, Caiyuan; Wan, Qijuan; Wu, Qisheng; Guo, Xiang; Qi, Jianfei; Ke, Yizhou; Ge, Hui; et al. (Frontiers in Marine Science, 2025)
The Portuguese oyster (Magallana angulata) is a valuable aquaculture species with sexual dimorphism in growth and nutritional traits, making it a promising candidate for sex-controlled breeding. However, the genetic mechanisms underlying its sex determination remain poorly understood. This study represents the first population-level investigation to identify sex-linked genetic markers and candidate genes in M. angulata using genome-wide association studies (GWAS) and transcriptomic analysis. A total of 1,613 sex-associated SNPs were identified, primarily located on Chr. 9 (7.99 Mb–10.51Mb). SNP annotation revealed 57 genes around these sex-associated SNPs. Transcriptomic analysis identified 8,635 differentially expressed genes (DEGs) between male and female gonads, of which 12 overlapped with GWAS-identified genes. Among these, four genes (5-HTR, ADPKD1-a, SCP, and SLC28A3) exhibited strong sex-specific genetic differentiation, with 5-HTR showing the most pronounced association. Further population genetic analysis revealed higher genetic diversity and heterozygosity of 5-HTR in males. Six sex-associated haplotypes based on SNPs within 5-HTR were constructed and validated in an independent population, although with reduced significance, suggesting both continuity and variation in sex determination mechanisms across populations. These findings provide a critical foundation for understanding the genetic basis of sex determination and advancing sex-controlled breeding strategies in M. angulata.